Security Challenges Behind the Development and Increased Use of Open Source Web Content Management Systems - Viduka, Dejan Zlatko; Kraguljac, Vladimir; Lavrnić, Igor (Journal of Information and Organizational Sciences, 2020)
Nowadays the IT market is enriched with free Open Source Web Content Systems offers that are available to all users. No system is perfect, and some of them have better solutions in one segment but are more vulnerable in others and vice versa, all in order to be more user-friendly. The most common form of Content Management System (CMS) implemented on the Internet today is the Web Content Management System(WCMS). This solution includes numerous advantages for site administrators as well as communication with the site designer for all users in order to improve the content, through written remarks, opinions and evaluations of the site content, resulting in a more dynamic and interactive site. This modern approach offers users with a poor IT background the opportunity to be independent and creative in creating their own website. In this paper we present data collected from several websites monitored for various cyber-attacks. Moreover, we will describe and analyze security challenges that follow cyber-attacks. During the monitoring process we followed 15 web addresses over a period of nine months and collected 520 reports of various cyber-attacks. The following analysis presents the different kinds of attacks, their frequency and some of the ways to reduce cyber-attacks to the lowest possible level.